2013
DOI: 10.1097/ta.0b013e31828fa3d3
|View full text |Cite
|
Sign up to set email alerts
|

A latent class model for defining severe hemorrhage

Abstract: Background Several predictive models have been developed to identify trauma patients who have had severe hemorrhage (SH) and may need a massive transfusion protocol (MTP). However, almost all these models define SH as the transfusion of ≥10 units of red blood cells (RBCs) within 24 hours of ED admission (aka massive transfusion, MT). This definition excludes some patients with SH, especially those who die before a 10th unit of RBCs could be transfused, which calls the validity of these prediction models into q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…High mortality rates during the first 24 h and rapid time course of massive hemorrhage make transfusion rate (e.g., ≥3 PRBC units/60 min) a more appropriate definition ( 4 ). In addition, data analysis from the PROMMT study enabled Rahbar et al to identify those patients most likely to develop massive hemorrhage based on emergency admission variables, such as systolic blood pressure, heart rate, pH, and hemoglobin ( 5 ). This prospective observational study showed that transfusion with higher ratio of plasma to PRBC early in resuscitation is associated with an improved survival at 24 h ( 6 ).…”
Section: Trauma Massive Hemorrhage and Trauma-induced Coagulopathy mentioning
confidence: 99%
“…High mortality rates during the first 24 h and rapid time course of massive hemorrhage make transfusion rate (e.g., ≥3 PRBC units/60 min) a more appropriate definition ( 4 ). In addition, data analysis from the PROMMT study enabled Rahbar et al to identify those patients most likely to develop massive hemorrhage based on emergency admission variables, such as systolic blood pressure, heart rate, pH, and hemoglobin ( 5 ). This prospective observational study showed that transfusion with higher ratio of plasma to PRBC early in resuscitation is associated with an improved survival at 24 h ( 6 ).…”
Section: Trauma Massive Hemorrhage and Trauma-induced Coagulopathy mentioning
confidence: 99%
“…The potential for survival bias has previously been described and estimated in studies of massive transfusion in adults. In one study, a latent class model classified injured adults as potentially needing or receiving a massive transfusion protocol (severe hemorrhage) based on several features, including the arrival vital signs, hemoglobin, and the ratios of plasma and platelets to red blood cells transfused 44,45 . In this model, most adults (84%) who died before receiving enough blood to meet the definition of massive transfusion were classified as severe hemorrhage, suggesting a survival bias in many patients when using blood volume to define significant hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Information on in-hospital mortality, complications, and later treatment were recorded daily from the medical record until death or discharge. Additional details regarding the design and main results of PROMMTT have been previously published [2,13,14,22]. …”
Section: Methodsmentioning
confidence: 99%